Perspectives on retro-tram in tourism - M. V. Maltseva; N. A. Zamyatina; A. V. Zbarskaya (Вестник университета)
Actualization of cultural heritage based on the nostalgic feeling of the good old days is one of the prospective trends in tourism development in times of crisis. Slowing down the pace of life and time perception are in strong demand due to the overall informatization, growing constraints and risk of uncertainty in the world. The study reveals the factors to manage time perception, describes the concept of the retro style and gives assessment to retro-tram in tourism basing on local and international practices. As a result of the research, the study suggests the concept of the sightseeing retro-tram from the perspectives of the human physiological perception and cultural studies while the results of the cross-case study analysis are summarized as a matrix of managerial recommendations so that to involve it in the tourism industry activities.